Pemanfaatan Instagram @Prokopimacehtengah Sebagai Strategi Humas Pemerintah Dalam Perspektif The Circular Model Of Some-Relations - Nanda Rezeki; Nursapia Harahap (STAI Bumi Silampari, 2026)
The development of information technology has forced government institutions to transform from a one-way linear communication pattern to an interactive digital public interaction. The Protocol and Communication Section of the Central Aceh Secretariat Leadership uses the @prokopimacehtengah Instagram account as the main channel for the dissemination of regional bureaucratic information. This study aims to analyze the public relations strategy of the Central Aceh regional government in managing cyber content and examine its application based on the perspective of The Circular Model of SoMe-Relations. The research method used is descriptive qualitative with a non-field cyber Qualitative Content Analysis approach through observation and documentation of digital artifacts in the period from March to May 2026, which is strengthened by the analysis of digital metrics (engagement rate and content reach). The results of the study show that in content management, public relations has consistently implemented a message channeling strategy that is divided into public policy clusters, leadership ceremonial activities, and local commodity branding. Judging from the theoretical analysis knife, the account has implemented the Share, Optimize, and Manage components to the maximum through informative visual packaging, the use of highlight features, and cyber narrative monitoring. However, the Engage aspect has not run optimally because admins tend to be passive, have a low engagement rate (0.45%), and implement a restrictive-preventive comment moderation policy. Public relations is recommended to improve dialogical communication in order to build full digital public trust.